Maintaining the Plurality and Sacred Value of Islamic Law through the Existence of the Sharia Banking Law - Waldi Nopriansyah; Makhrus Munajat; Abdul Mujib (Faculty of Sharia and Law, Universitas Islam Negeri (UIN) Walisongo Semarang, 2022)
Islamic banks are the fastest growing Islamic financial institutions in Indonesia. In fact, Islamic Banks already have special regulations, namely Law Number 21 of 2008. This article aimed to analyze how important the Sharia Banking Law is in maintaining the plurality and sacredness of Islamic law in every sharia banking operational activity. The method used in this article is qualitative with a normative approach. This article found that Sharia Banking Law supports the sacredness of Islamic law, namely to realize the benefit. The existence of the Sharia Banking Law indirectly shows its capacity as a legal product that provides a plurality space so that the law can be enjoyed by all humans and all religions based on community beliefs. In addition, the existence of the Sharia Banking Law can also be a reference for other Islamic law products to provide a plurality value space behind the sacredness of Islamic law in Indonesia.